2014
DOI: 10.1371/journal.pone.0112382
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Flagellum Volume Determines Freezability in Red Deer Spermatozoa

Abstract: The factors affecting the inter-individual differences in sperm freezability is a major line of research in spermatology. Poor sperm freezability is mainly characterised by a low sperm velocity, which in turn is associated with low fertility rates in most animal species. Studies concerning the implications of sperm morphometry on freezability are quite limited, and most of them are based on sperm head size regardless of the structural parts of the flagellum, which provides sperm motility. Here, for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…The differences between studies could be due to the species. Shape and size of the sperm head and the flagellum are factors that define the cryosensivity of the cell [4,33,35]. A small size of head has been related with a higher cryoresistance in some species [4].…”
Section: Discussionmentioning
confidence: 99%
“…The differences between studies could be due to the species. Shape and size of the sperm head and the flagellum are factors that define the cryosensivity of the cell [4,33,35]. A small size of head has been related with a higher cryoresistance in some species [4].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have explored the morphological response to diluting or washing the sperm sample,105106 to capacitation107 or to cryopreservation 26108109110…”
Section: Assessment Of Sperm Morphometry II – Functional Aspectsmentioning
confidence: 99%
“…Despite most of the studies on the effect of cryopreservation on sperm morphology have been focused on the evaluation of sperm head features, Ros-Santaella et al 109. recently reported that stags not differing in sperm head dimensions showed significant differences in sperm cryoresistance that were strongly related to the volume of the sperm principal piece.…”
Section: Assessment Of Sperm Morphometry II – Functional Aspectsmentioning
confidence: 99%
See 2 more Smart Citations